Cellulose Nanocrystal:Polymer Hybrid Optical Diffusers for Index‐Matching‐Free Light Management in Optoelectronic Devices. Issue 21 (25th August 2017) - Mahpeykar, Seyed Milad; Zhao, Yongbiao; Li, Xiyan; Yang, Zhenyu; Xu, Qiwei; Lu, Zheng‐Hong; Sargent, Edward H.; Wang, Xihua
Abstract: A novel optical diffuser based on cellulose nanocrystals (CNCs) embedded in polydimethylsiloxane (PDMS) matrix, or cellulose nanocrystal:polymer (CNP) is reported. By offering simple low‐cost fabrication process as well as compatibility with large‐scale production, the proposed optical diffuser is a better choice for integration into optoelectronic devices for light management compared to other cellulose‐based diffusers due to its physical durability and the lack of requirement for index‐matching between the diffuser and the optoelectronic device thanks to the unique surface properties, mechanical flexibility, and optical transparency offered by PDMS as the matrix material. It is demonstrated that CNCs are an excellent filler material to pair up with PDMS in an optical diffuser providing highly efficient broadband light diffusion in visible and near‐infrared range of light at very low concentrations (≈1 wt%). At its optimized form, a CNP hybrid optical diffuser is capable of achieving very high haze values (up to 85%) while maintaining a high degree of transparency (≈85%) at the same time. As a proof of concept, light management capabilities of CNP hybrid optical diffusers are leveraged to demonstrate their potential for light extraction improvement in organic light‐emitting diodes and light absorption enhancement in thin‐film solar cells. Abstract : Light management is an essential necessity for emerging optoelectronic devices with low efficiency. A new class of optical diffusers is reported by leveraging cellulose nanocrystals embedded in a polymer matrix. Taking advantage of widely used and cheap materials together with facile fabrication, the proposed optical diffuser provides efficient light management for common optoelectronic devices without any third‐party index‐matching requirement.